Understanding fan tourists at a non-commodified fan pilgrimage site: an application of fan capital theory. Issue 1 (2nd January 2023) - Thelen, Timo; Kim, Sangkyun
ABSTRACT: This study aims to examine how fan tourism emerges at a non-commodified touristic site and what constitutes meaningful, (in)authentic fan tourism experiences. The research focus is on Japanese fan tourists visiting the officially denied Attack on Titan media pilgrimage site in Nördlingen, Germany. Drawing on fan capital theory from fan studies, the findings suggest that two types of fan capital, namely fan cultural capital and fan symbolic capital, played an important role in establishing Nördlingen as a quasi-authentic fan pilgrimage site. Research suggests not only the absence of commodification at the site, but also fostering of the fan tourists' imagination and affection with the site. Exclusivity and performativity of fan activities in situ were observed.